Application of ANFIS system in prediction of machining parameters - Shirdar, Mostafa Rezazadeh; Nilashi, Mehrbakhsh; Bagherifard, Karamollah; Ibrahim, Othman; Izman, S.; Moradifard, Hossein; Janahmadi, Nasim; Barisamy, Mehdi (Asian Research Publishing Network (ARPN), 2011)

(untitled)
Since cutting conditions have an influence on reducing the production cost and time of machining process and also the quality of a final product the prediction of output machining parameters such as surface roughness and tool life criteria for different cutting speed, feed rate, depth of cut and tool geometry is one of vital modules in process planning of metal parts. In this study with use of experimental results on machining of ST-37 and subsequently, ANFIS system, importance of each parameter was studied. These parameters were considered as input in order to predict the surface finish and tool life criteria, two conflicting objectives, as the process performance. In this paper ANFIS system was applied to predict output parameters of machining. Results show that amount of input influence on the outputs parameters. By using ANFIS input parameters entered to ANFIS system then all training data was trained with 300 epochs. After training the value of error which is 1.039e-006 was calculated.